2022
DOI: 10.1002/ncp.10860
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition risk assessed by Nutritional Risk Screening 2002 is associated with in‐hospital mortality in older patients with COVID‐19

Abstract: Background Although numerous studies have been performed to determine predictors of coronavirus disease 2019 (COVID‐19) mortality, studies that address the geriatric age group are limited. The aim of this study was to investigate the utility of the Nutritional Risk Screening 2002 (NRS‐2002) and the Geriatric 8 (G8) screening tools in predicting clinical outcomes in older adults hospitalized with COVID‐19. Methods Patients aged ≥60 years who were hospitalized with COVID‐19 in the second wave of the pandemic wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…One study reviewed 4,187 hospitalized COVID-19 patients and revealed ten-fold higher odds of mortality among those who were malnourished relative to well-nourished individuals [ 19 ]. Another study on older, hospitalized COVID-19 patients also independently linked older age and higher NRS‐2002 scores with in‐hospital mortality [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study reviewed 4,187 hospitalized COVID-19 patients and revealed ten-fold higher odds of mortality among those who were malnourished relative to well-nourished individuals [ 19 ]. Another study on older, hospitalized COVID-19 patients also independently linked older age and higher NRS‐2002 scores with in‐hospital mortality [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study, which compared four different nutritional risk screening tools, found that the NRS-2002 was more successful than others in recognizing malnutrition in COVID-19 21 . Although the number of studies evaluating the relationship between COVID-19 and malnutrition is small, most of these studies found that malnutrition was an important risk factor for COVID-19-related mortality 2 . Early implementation of nutritional support may have reduced the mortality rate of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported that older age was the main risk factor for COVID-19 mortality 2,3 . With aging, the immune system is more prone to infections, impaired cell-mediated and humoral immunity, and pro-inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines suggest implementation of a nutrition risk screening tool to identify high risk patients requiring nutrition interventions [ 1 ••]. Early evaluation (within 48 h of admission) is required to identify pre-existing malnutrition and those at high risk of developing malnutrition [ 12 ]. There are multiple validated tools that can be utilized to determine the level of nutritional risk, such as Nutrition Risk Screening 2002 (NRS-2002), Malnutrition Screening Tool (MST) or Malnutrition Universal Screening Tool (MUST), and The Nutrition Risk in Critically ill (NUTRIC) [ 3 ••, 13 ].…”
Section: Nutrition Assessmentmentioning
confidence: 99%